STUDY THE EFFECT OF NON-THERMAL PLASMA ON LOCAL ISOLATE OF E. COLI - Hussein G. Hassan; Intesar H. Hashim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
In this endeavor, three types of non-thermal dielectric barrier discharge plasma (NTDBDP) systems are designed and built locally in custom configurations and investigate the properties of the produced plasma. The difference between these systems is the shape and configuration of the discharge electrode, which plays an essential role in defining the nature of the generated plasma. The first type is two circular plane copper discs, the second is two concentric circular rings of copper, and the third is two concentric cylindrical tubes. Quartz was used as a plate or tube as dielectric material. The optical emission spectroscopy (OES) method was used to analyze the produced plasma spectrum and calculate the various plasma properties (the temperature of electrons, the density of electrons, the frequency of electrons, the Debye length, and the Debye number) in different conditions of applied voltage for all designs. The generated non-thermal plasma was used to inactivate E.coli bacteria at different AC applied voltages (18, 20 and 22 kV) and plasma exposure durations (10, 15, and 20 min). The effect of non-thermal plasma was slight on the bacteria at low applied voltage and exposure time. In contrast, the impact positively of the high voltage and treatment time values on the bacteria. The plasma effect appeared effective at these voltages due to the homogeneously and high intensity of produced plasma and high temperature of plasma electrons. Thus, the effect is more effective on bacteria. The re-cultivation of the treated bacteria demonstrated this, as the spread was very little. All operating scenarios had an electron temperature of around , while the electron density was . The results demonstrated the distinct effect of electrode configurations on the properties of the produced plasma due to a change in the electric field’s distribution in the discharge region, which allowed it to be used in E. coli bacteria inactivation.